The Taxonomy of SME’s Organizational Culture in Padang City Based on Competing Value Framework - Sulastri1, Yuki Fitria, Chichi Andriani (International Journal of Advanced Science and Technology, 2020)
This study aims to determine the factors forming organizational culture in the city of Padang SME’s as well as determine the factors that cause inconsistencies in organizational culture in the city of Padang. The population in this study were all SME’s in Padang, which amounted to 2,953 SME’s. The sampling technique was using a proportional sample cluster area technique with company criteria with 3-5 employees and total assets of Rp.10,000,000 per year so that the samples obtained in this study there was 321 SME’s spread proportionally in 11 districts of Padang city. Data collection in this study is to use a questionnaire with data analysis techniques using dummy regression analysis. The results of data processing showed that the variables of gender, age, educational background, length of business, total assets and marital status did not have an influence in the formation of the organizational culture of the city of Padang, but the leadership variable had an influence on the formation of the organization's culture in the city of Padang. The results also showed that the inconsistency of the organizational culture of the city of Padang was caused by the lack of leadership knowledge on organizational culture, the style of the leader/owner of the company, the relatively new age of the company, the small scale of the company, low turnover, low educational background, age relatively young and influential company owners do not yet have legal entity status for their businesses.